A New Route to Phenols: Palladium‐Catalyzed Cyclization and Oxidation of γ, δ‐Unsaturated Ketones. Issue 15 (13th July 2016) - Samadi, Sadaf; Orellana, Arturo
Abstract: We report a new strategy for the synthesis of phenols from acyclic unsaturated ketones in one pot. The reaction proceeds by palladium‐catalyzed carbopalladation of an alkene with the enol form of the tethered ketone, generating a substituted cyclohexanone. Upon introduction of a terminal oxidant a palladium‐catalyzed oxidation ensues to give the desired phenol. This approach allows the programming of phenol substituents on the acyclic substrate and therefore circumvents the limitations inherent in traditional syntheses of phenols. Abstract : 2‐in‐1 : A new strategy for the synthesis of substituted phenols from acyclic unsaturated ketones is described. The reaction features sequential redox‐neutral palladium‐catalyzed cyclization and palladium‐catalyzed oxidation steps. This approach to phenols enables pre‐programming of substituents on the acyclic system, and circumvents selectivity issues frequently encountered in the functionalization of phenols.